STAT1 deficiency underlies a proinflammatory imprint of naive CD4+ T cells in spondyloarthritis - Cherqaoui, Bilade; Crémazy, Frédéric; Lauraine, Marc; Shammas, Ghazal; Said-Nahal, Roula; Mambu Mambueni, Hendrick; Costantino, Félicie; Fourmont, Marine; Hulot, Audrey; Garchon, Henri-Jean; Glatigny, Simon; Araujo, Luiza M.; et al. (Frontiers in Immunology, 2023)
In spondyloarthritis (SpA), an increased type 3 immune response, including T helper cells (Th) 17 excess, is observed in both human and SpA animal models, such as the HLA-B27/human β2-microglobulin transgenic rat (B27-rat). To investigate this unexplained Th17-biased differentiation, we focused on understanding the immunobiology of B27-rat naive CD4+ T cells (Tn). We observed that neutrally stimulated B27-rat Tn developed heightened Th17 profile even before disease onset, suggesting an intrinsic proinflammatory predisposition. In parallel with this observation, transcriptomic and epigenomic analysis showed that B27-rat Tn exhibited a decreased expression of Interferon/Th1- and increased expression of Th17-related genes. This molecular signature was predicted to be related to an imbalance of STAT1/STAT3 transcription factors activity. Stat1 mRNA and STAT1 protein expression were decreased before disease onset in Tn, even in their thymic precursors, whereas Stat3/STAT3 expression increased upon disease establishment. Confirming the relevance of these results, STAT1 mRNA expression was also decreased in Tn from SpA patients, as compared with healthy controls and rheumatoid arthritis patients. Finally, stimulation of B27-rat Tn with a selective STAT1 activator abolished this preferential IL-17A expression, suggesting that STAT1 altered activity in B27-rats allows Th17 differentiation. Altogether, B27-rat Tn harbor a STAT1 deficiency preceding disease onset, that may occur during their thymic differentiation, secondarily associated with a persistent Th17 bias, which is imprinted at the epigenomic level. This early molecular phenomenon might lead to the persistent proinflammatory skew of CD4+ T cells in SpA patients, thus offering new clues to better understand and treat SpA.